Đáp án:
Đáp án: e, m=3 hoặc m=5/3
f,m= (3+3 √5)/2 hoặc m= (3-3 √5)/2
Giải thích các bước giải:
e, x^2-(m-2)x+m(m-3)=0
theo viet => x1+x2= m-2
x1x2= m(m-3)
mà x1+2x2=1
=> x1=3-m
và x2= 2m-5
=> (3-m)(2m-5)=m(m-3)
=> (m-3)(m+2m-5)=0
<=> m=3 hoặc m=5/3
f, x^2-(m+3)x+2(m+2) =0
theo viet x1+x2= m+3 và x1x2= 2(m+2)
mà x1=2x2
=> 3x2= m+3
=> x2= (m+3)/3 => x1= 2(m+3)/3
=> (m+3)/3 . 2(m+3)/3=2(m+2)
<=> (m+3)^2= 9(m+2)
<=> m^2-3m-9=0
<=> m= (3+3 √5)/2 hoặc m= (3-3 √5)/2
Hãy luôn nhớ cảm ơn và vote 5*
nếu câu trả lời hữu ích nhé!